(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
One hundred and sixty-nine samples of urine have been collected through the period from December/2016 to May/2017. Were for isolation and identification of Proteus mirabilis. Isolated from urine in patients with UTI. Identification was done by grow- ing on different media and biochemical tests as well as the antibiotics susceptibility were studied by using twenty types of antibiotics at acidic pH, neutral pH and alkaline or basic pH by disc diffusion method. These antibiotics were involved Ciprofloxacin, Amikcin, Meromenem, Imipenem, Ampicillin, Rifampin, Gentamicin, Trimethoprim, Tetracycline, Amoxicillin, Sulfamethoxazole, Carbnicillin, Rifaximin, Penicillin-G, Ox- olinic acid, Bacitracin, Clindamycin, Erthromycin, Novamicin and Aztreomycin. The Ciprofloxacin and Aztreomycin have high activity at both acidic and neutral pH, while the Amikcin, Meromenem, Imipenem and Ciprofloxacin have high activity at basicity pH against these bacteria.